The EU and Russia: Conflicts and potentials of a difficult partnership - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2007)
Russia and the EU are entering an important stage in their relations. January sees the beginning of negotiations over the future of the Partnership and Cooperation Agreement (PCA), which expires in November 2007. Germany's EU Presidency in the first half of 2007 will coincide with the decisive phase of negotiations.This study takes a closer look at the way Russia-EU relations have developed since the PCA was first concluded in 1997. Although the relationship has grown steadily broader and deeper over the past fifteen years, it is today characterized by political and value differences and growing rivalry in the post-Soviet region. Antidemocratic tendencies in Russia clash with the EU's wish to use its foreign policy to promote democracy and human rights in partner states.The study measures the PCA's aims against the reality of Russia-EU relations, and considers whether the normative goals of the PCA can actually have any influence on the course of the Russian transformation. At the end a brief survey of the Russian and European debates about Russia-EU relations shows where the decisive fault lines run between the different standpoints.On the basis of this - certainly sobering - analysis the study makes the following recommendations for German and EU policy. Negotiations over the follow-up agreement should do without inflated normative goals. The factual pragmatism of EU policy has repeatedly subverted such goals in recent years anyway - and in the process done nothing to improve its credibility. Additionally, EU policy in the post-Soviet region should be multilateralized in order to prevent the region becoming even more polarized between Moscow and Brussels. (SWP Research Papers)
Keywords: 320; Europäische Union